2020
DOI: 10.3892/or.2020.7495
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane suppresses carcinogenesis of colorectal cancer through the ERK/Nrf2‑UDP glucuronosyltransferase 1A metabolic axis activation

Abstract: The long pre-cancerous state of colorectal cancer (CRC) provides an opportunity to prevent the occurrence and development of CRC. The detoxification of CRC food-borne carcinogenic heterocyclic amines is highly dependent on UDP glucuronosyltransferase 1A (UGT1A)-mediated glucuronidation. Sulforaphane (SFN), a phytochemical, possesses antioxidant, anti-inflammatory and anticarcinogenic effects on the prevention of CRC. Previous studies revealed that SFN upregulates the expression of UGT1A. The aim of the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…For example, in the absence of Nrf2 gene activity, the mitochondria-dependent protection by broccoli extract or sulforaphane from pulmonary injury is almost abolished [49], as is the PI3K-AKT-dependent protection by Withania from liver injury [99], or the hemooxygenase-1-dependent protection by curcumin or phenethyl isothiocyanate from inflammatory stress [50]. The extracellular-signal-regulated kinase (ERK) forms a signaling pathway together with Nrf2 [100,101], as does AMPK with Nrf2 [102]. Sirtuin-1 and Nrf2 represent another joint pathway induced by phytochemicals [103].…”
Section: Phytochemicals and Health-a Broader Perspectivementioning
confidence: 99%
“…For example, in the absence of Nrf2 gene activity, the mitochondria-dependent protection by broccoli extract or sulforaphane from pulmonary injury is almost abolished [49], as is the PI3K-AKT-dependent protection by Withania from liver injury [99], or the hemooxygenase-1-dependent protection by curcumin or phenethyl isothiocyanate from inflammatory stress [50]. The extracellular-signal-regulated kinase (ERK) forms a signaling pathway together with Nrf2 [100,101], as does AMPK with Nrf2 [102]. Sirtuin-1 and Nrf2 represent another joint pathway induced by phytochemicals [103].…”
Section: Phytochemicals and Health-a Broader Perspectivementioning
confidence: 99%
“…Without doubt, the most controversial outcome of prolonged and gain-of-function Nrf2 activation concerns cancer progression [ [224] , [225] , [226] ]. It is well established that cytoprotection elicited through Nrf2 activation is important for the suppression of carcinogenesis in the first instance [ [227] , [228] , [229] , [230] ]. However, Nrf2 activity in aggressively malignant cells promotes tumorigenesis and metastasis [ 228 , [231] , [232] , [233] ], increases resistance to platinum-based chemotherapy [ 224 , [234] , [235] , [236] , [237] ] and has been associated with overall poorer prognosis [ 238 ].…”
Section: Balancing the Argument: Could Too Much Nrf2 Be Detrimental?mentioning
confidence: 99%
“…Regarding these reports, the ingestion of Nrf2-activating phytochemicals including SFN could be harmful to colorectal cancer patients carrying the WT p53 gene. However, other studies have reported that SFN increases the nuclear translocation of Nrf2, inhibits cell proliferation and colony formation, and induces apoptosis in colon cancer HT-29 and SW480 cells [ 136 ].…”
Section: Regulation Of Nrf2/keap1 By Phytochemicals In Colorectal Cancermentioning
confidence: 99%